Phytochemical Analysis and Determination of Phytochemical Compositions of Various Extracts from the Twigs of Some Selected Plants Used as Chewing Sticks in Nigeria - , Amaechi J.C; , Okereke J.N (Archives of Current Research International, 2024)
Chewing sticks have been identified as potential tools for teeth cleaning and protection against dental conditions, including caries. This study determined the phytochemical composition of specific medicinal plants commonly utilized as chewing sticks by determining the qualitative and quantitative composition in various medicinal plants used as chewing sticks: bitter leaf, orange, neem, napoleanna, kolanut, and guava. Chewing sticks from bitter leaf, orange, neem, napoleanna, kolanut and guava plants have been used as tooth cleaner. Additionally, these chewing sticks protect against several dental conditions including caries. This study aimed to analyze the presence of various classes of phytochemicals and to determine their compositions in various extracts obtained from the twigs of these plants. Soxhlet extraction of the plants were done using standard method and aqueous, methanolic and ethanolic extracts of the plants were used for their various phytochemicals. The investigation focused on alkaloids, flavonoids, tannins, saponins, steroids, and glycosides, examining their concentrations in aqueous, ethanolic, and methanolic extracts. Bitter leaf extracts exhibited substantial levels of alkaloids (methanolic: 47.44%, ethanolic: 43.73%, aqueous: 35.9%) and flavonoids (methanolic: 12.28%, ethanolic: 8.85%, aqueous: 5.05%). Tannin content was higher in aqueous extracts (4.92%) compared to ethanolic (4.59%) and methanolic (4.35%) extracts. Saponin levels were highest in aqueous extracts (18.83%), while steroids (0.86%) and glycosides (0.48%) were predominant in methanolic extracts. Quantitative analysis of orange extracts revealed elevated steroid and glycoside levels in methanolic extracts. Neem extracts consistently displayed high concentrations of steroids and glycosides across all solvents, with statistical analysis indicating no significant differences (p>0.05). Napoleanna extracts showcased variations in alkaloid (ethanolic: 0.59%), flavonoid (aqueous: 6.72%), tannin (methanolic: 0.37%), saponin (methanolic: 4.27%), steroid (aqueous: 0.22%), and glycoside (ethanolic: 0.37%) content. Kolanut extracts exhibited high alkaloid, tannin, and steroid levels across all extracts, with glycosides prominent in aqueous and ethanolic extracts. Guava extracts demonstrated varying concentrations of alkaloids (methanolic: 0.87%, aqueous: 0.18%), flavonoids (ethanolic: 1.60%, methanolic: 1.08%), tannins (methanolic: 1.09%, ethanolic: 0.83%), saponins (methanolic: 3.28%, ethanolic: 0.92%), steroids (methanolic: 1.13%, ethanolic: 0.43%), and glycosides (methanolic: 0.46%, ethanolic: 0.02%). Statistical analysis revealed no significant differences (p>0.05) in the phytochemical amounts among the tested extracts for each plant.